Influence of Gurney Flap and Leading-Edge/Trailing-Edge Flaps on the Stall Characteristics and Aeroacoustic Performance of Airfoils - Zelin Liu; Kaidi Li; Xiaojing Sun (Fluids, 2025)
In aerospace, flow control techniques have improved the separation flow characteristics around airfoils by various means. In this paper, the delayed detached eddy simulation (DDES) technique is used to simulate the detailed flow field around the NACA0021 airfoil with two different flow control methods (Gurney flaps and leading- and trailing-edge flaps) applied at an angle of attack of 20°. The aerodynamic characteristics around the airfoil under these two flow control methods are investigated, and the results show that both flow control methods lead to a significant increase in the pressure on the suction surface of the airfoil, which contributes to an increase in lift. The aeroacoustic characteristics of the original airfoil, the Gurney flapped airfoil and the airfoil with leading-edge and trailing-edge flaps are then analyzed using a combination of DDES and FW-H acoustic analog equations. The results show that the total sound pressure level of the Gurney flap airfoil and the leading-edge and trailing-edge flap airfoil are improved in most azimuthal angles of the acoustic pointing distribution, among which the degree of improvement of the leading-edge and trailing-edge flap airfoil is greater than that of the Gurney flap airfoil near the trailing edge, and the total sound pressure level of the band leading- and trailing-edge flap airfoil decreases in the azimuthal angles near the leading edge. Compared with the original airfoil, the noise value is thus reduced by up to 4.13 dB. The results of pressure pulsation cloud map, sound pressure level cloud map on the airfoil surface and vortex cloud map distribution show that the two flow controls increase the pressure pulsation near the trailing edge, the range and peak value of sound emission on the airfoil surface increase, and the trailing vortex becomes more finely grained, which leads to an increase in noise.